Transformations in the L2 self: Changing motivation in a study abroad context. (November 2018) - Fryer, Mitchell; Roger, Peter
Abstract: This research investigates the study abroad experiences of eight Japanese university students through a longitudinal study of changes in the second language (L2) self. Semi-structured interviews and photo narrative journals were used to explore short-term and long-term changes in the participants' L2 motivational self systems and the effects of these changes on motivation, study goals and learning behaviours. Three distinct patterns emerged, each of which appeared to have a significant influence on motivation and study behaviours in the short and long-term. For the first group, positive L2 experiences made much clearer the discrepancies between current and desired states, creating an empowering sense of moving closer to the ideal L2 self. For the second group, individuals' self images became characterised by both an ideal self and a complementary ought-to self. The third group comprised those participants who described a feared self which they linked to their perceived inability to engage with the target language community in ways that they had hoped. Overall, our findings demonstrate the power of short-term study abroad to provide an opportunity for individuals to experience possible futures, with sustained effects on the clarity and availability of their future self visions and motivated language learning behaviours.